2008
DOI: 10.1002/cbic.200700670
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Evaluation of a CYP106A2 Low Homology Model and Production of Mutants with Changed Activity and Selectivity of Hydroxylation

Abstract: Steroids are important pharmaceutically active compounds. In contrast to the liver drug-metabolising cytochrome P450s, which metabolise a variety of substrates, steroid hydroxylases generally display a rather narrow substrate specificity. It is therefore a challenging goal to change their regio- and stereoselectivity. CYP106A2 is one of only a few bacterial steroid hydroxylases and hydroxylates 3-oxo-Delta4-steroids mainly in 15beta-position. In order to gain insights into the structure and function of this en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…[13,14] As an example, the 11a-hydroxylation activity could be increased up to elevenfold. [29] In summary, this concept for CYP106A2-catalyzed hydroxylation presents a simple and efficient approach towards the preparative scale synthesis of hydroxylated steroid derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] As an example, the 11a-hydroxylation activity could be increased up to elevenfold. [29] In summary, this concept for CYP106A2-catalyzed hydroxylation presents a simple and efficient approach towards the preparative scale synthesis of hydroxylated steroid derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies with structurally related compounds showed the conversion of abietic acid to 12α-and 12β-hydroxyabietic acid, respectively (see Scheme 4). The existence of many mutants of CYP106A2, created by directed evolution as well as rational protein design [74,75], provides an excellent source to exploit the potential of this P450 for further biotechnological applications. Due to their diverse biological properties, the production of hydroxylated diterpene derivatives could be especially useful for the pharmaceutical industry.…”
Section: Resin Acid Diterpenoidsmentioning
confidence: 99%
“…To gain further insights into the structural basis of the regioselectivity of hydroxylation, we used a homology model recently created in our group [9] to dock abietic acid into the active site with the aid of the program FlexX. [22,23] The best docking orientations for hydroxylation in the a (yellow) and b (cyan) positions ( Figure 3) revealed possible hydrogen bonds between the acid group of the substrate and the side chains of the residues D295, E78, and R66.…”
Section: Substrate Dockingmentioning
confidence: 99%
“…[9] Molecular docking calculations were performed for 580 www.chembiochem.org the substrate abietic acid. For the calculations, the FlexX docking program was used.…”
Section: Modeling and Dockingmentioning
confidence: 99%
See 1 more Smart Citation